2022
DOI: 10.2147/ijgm.s384119
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Klotho and SIRT1 Expression in Renal Aging Related Disease

Abstract: Background This study focused on renal arteriosclerosis and aimed to explore the relationship between Klotho and SIRT1 by morphological staining, which will help to provide new ideas for the treatment of renal-aging-related diseases and a theoretical basis for the development of new drugs. Methods Kidney tissue samples were collected from patients who underwent nephrectomy. HK-2 cells were cultured. The Hematoxylin-eosin (HE) staining, Periodic Acid-Schiff (PAS) stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have shown Sirtuin 1 is involved in insulin release and the regulation of klotho. Klotho may antagonize oxidative stress, activate cellular autophagy, and inhibit neuroinflammation to reduce cognitive impairment by affecting the AMPK/SIRT1 signaling pathway, which plays an important role in glucose regulation, neuron proliferation, oxidative stress, and cognition ( 30 32 ).. Klotho also upregulates antioxidant enzymes like superoxide dismutase to bolster neuronal defenses against oxidative damage ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown Sirtuin 1 is involved in insulin release and the regulation of klotho. Klotho may antagonize oxidative stress, activate cellular autophagy, and inhibit neuroinflammation to reduce cognitive impairment by affecting the AMPK/SIRT1 signaling pathway, which plays an important role in glucose regulation, neuron proliferation, oxidative stress, and cognition ( 30 32 ).. Klotho also upregulates antioxidant enzymes like superoxide dismutase to bolster neuronal defenses against oxidative damage ( 33 ).…”
Section: Discussionmentioning
confidence: 99%